Controlling the Directed Quantum Transport of Ultracold Atoms in an Optical Lattice with a Periodic Driving Field. (1st February 2015) - Dong, Dong; Gong, Ming; Zou, Xu-Bo; Guo, Guang-Can
Abstract We propose a new method to control the directed quantum transport of ultracold atoms in a one-dimensional optical lattice. In this proposal, the effective tunneling between the neighboring sites can be adjusted via coherent destruction of tunneling by tuning the phase of the external field, instead of using the driving field intensity or the frequency, thus the directed quantum transport of ultracold atoms can be coherently controlled in a much easier manner. Our proposal overcomes the major drawback of the method used by Creffield et al. [Phys. Rev. Lett. 99 (2007) 110501], and can be implemented, in principle, in any one-dimensional optical lattice. Some potential applications of the scheme are also discussed.